2020
DOI: 10.3347/kjp.2020.58.1.7
|View full text |Cite
|
Sign up to set email alerts
|

4-Hydroxybenzaldehyde Restricts the Intracellular Growth of Toxoplasma gondii by Inducing SIRT1-Mediated Autophagy in Macrophages

Abstract: <i>Toxoplasma gondii</i> is an intracellular protozoan parasite that infects approximately one third of the human popu- lation worldwide. Considering the toxicity and side effects of anti-toxoplasma medications, it is important to develop effec- tive drug alternatives with fewer and less severe off-target effects. In this study, we found that 4-hydroxybenzaldehyde (4- HBA) induced autophagy and the expression of NAD-dependent protein deacetylase sirtuin-1 (SIRT1) in primary murine bone marrow-deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 36 publications
0
17
1
Order By: Relevance
“…More recent studies evaluated 4-hydroxybenzaldehyde (4-HBA) ( Lee et al, 2020 ). 4-HBA-induced anti- T. gondii activity in BMDM seemed to be mediated by autophagy ( Lee et al, 2020 ).…”
Section: Potential Therapeutic Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recent studies evaluated 4-hydroxybenzaldehyde (4-HBA) ( Lee et al, 2020 ). 4-HBA-induced anti- T. gondii activity in BMDM seemed to be mediated by autophagy ( Lee et al, 2020 ).…”
Section: Potential Therapeutic Implicationsmentioning
confidence: 99%
“…More recent studies evaluated 4-hydroxybenzaldehyde (4-HBA) ( Lee et al, 2020 ). 4-HBA-induced anti- T. gondii activity in BMDM seemed to be mediated by autophagy ( Lee et al, 2020 ). 4-HBA seems to act via sirtuin-1 (SIRT1), a nicotine adenine dinucleotide-dependent protein deacetylase that can stimulate autophagy ( Lee et al, 2020 ).…”
Section: Potential Therapeutic Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the mechanism by which autophagy is initiated, it can be divided into the canonical autophagy and the non-canonical autophagy [10]. It has been reported that T. gondii infection could induce autophagy in many mammalian cells including Hela cells and murine bone marrow derived macrophages(BMDMs), suggesting the critical role of autophagy in antiparasitic responses of host cells [11]. For example, IFN-γ could induce non-canonical autophagy by recruitment of γ-aminobutyric acid (GABA) receptor-associated protein-like 2 (GABARAPL2), causing growth restriction of T.gondii in Hela cells [12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, autophagy is thought to be an integral component of the innate immune response, targeting intracellular parasites, and parasites in damaged vacuoles and phagosomes, limiting their growth (Huang and Brumell, 2014). Recent study has shown that 4-Hydroxybenzaldehyde restricts the intracellular growth of Toxoplasma by activating SIRT1-mediated autophagy in macrophages (Lee et al, 2020). However, intracellular pathogens have also evolved diverse mechanisms to avoid autophagy (Steele et al, 2015).…”
Section: Introductionmentioning
confidence: 99%